2014
DOI: 10.1155/2014/175721
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p63 Protein Stability via Ubiquitin-Proteasome Pathway

Abstract: The p53-related p63 gene encodes multiple protein isoforms, which are involved in a variety of biological activities. p63 protein stability is mainly regulated by the ubiquitin-dependent proteasomal degradation pathway. Several ubiquitin E3 ligases have been identified and some protein kinases as well as other kinds of proteins are involved in regulation of p63 protein stability. These regulators are responsive to diverse extracellular signaling, resulting in changes of the p63 protein levels and impacting dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 68 publications
0
28
1
1
Order By: Relevance
“…In addition, dramatic reduction in p63 levels that follows PKD3 silencing suggests that a role for PKD3 signaling in p63 stabilization. Because of key roles of p63 in cell growth and proliferation, apoptosis and differentiation, p63 levels are tightly regulated, mainly by the ubiquitin-dependent proteasomal degradation pathway (38). Recent studies have shown that degradation of p63 during KC differentiation by E3 ubiquitin ligase requires GSK3 kinase activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dramatic reduction in p63 levels that follows PKD3 silencing suggests that a role for PKD3 signaling in p63 stabilization. Because of key roles of p63 in cell growth and proliferation, apoptosis and differentiation, p63 levels are tightly regulated, mainly by the ubiquitin-dependent proteasomal degradation pathway (38). Recent studies have shown that degradation of p63 during KC differentiation by E3 ubiquitin ligase requires GSK3 kinase activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…). Mutations in the TP63 gene have been associated with human developmental diseases and skin abnormalities (Li & Xiao , Soares & Zhou ), as well as with different cancer types, such as lung, breast, bladder and squamous cell carcinoma (Hu et al . , Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that ΔNp63α is the predominant isoform of p63 expressed in epithelial cells. Studies have shown that p63 proteins can function as transcription factors, controlling transcription of downstream genes, including p21, Bax, Puma, Dicer, MKP3, and genes involved in cell adhesion [5]. Consequently, p63 proteins play a key role in cell proliferation, survival, development and tumorigenesis [6].…”
Section: Introductionmentioning
confidence: 99%